ANALISIS PAPARAN KADMIUM (Cd) DALAM DARAH TERHADAP KADAR SGOT DAN SGPT PADA PEROKOK AKTIF DAN PEROKOK PASIF DI WARUNG KOPI WILAYAH SURABAYA TIMUR - Febri, Fitra Nur; Indah, Lestari; Christ Kartika , Rahayuningsih (Analis Kesehatan Sains, 2021)
Cadmium is one of the chemicals contained in cigarettes, when consumed by humans in the long term and with sufficient intensity often can damage human organs such as the liver. This study aims to determine the exposure of cadmium to the levels of SGOT and SGPT in active smokers and passive smokers in a coffee shop in East Surabaya. This study used a correlational type of research, with a cross-sectional research design. There were 30 respondents who were divided into 2 groups, namely 15 active smokers and 15 passive smokers in a coffee shop in East Surabaya. The examination of cadmium used an Atomic Absorption Spectrophotomter (AAS), while the examination of SGOT and SGPT used the IFCC method (kinetic) with a photometer. The data were analyzed by Kolmogorov-Sminorv test and r-Pearson test. The results showed that there was no effect of high cadmium exposure in active smokers and passive smokers on SGOT and SGPT levels. The average cadmium in active smokers and passive smokers were 2.93 g/L and 1.30 g/L. while the levels of SGOT and SGPT in active smokers were 27.26 U/L and 36.86 U/L. The average levels of SGOT and SGPT in passive smokers were 19.73 U/L and 17.86, respectively. In these results it can be seen that the increase in cadmium levels does not affect liver function cells.